Innovative contextualized instructional materials utilizing ethanolic crude extract from blue porter weed (Stachytarpheta Jamaicensis) for enhancing science learning in the Philippines - Ondrada, Joyrem J.; Mario, Julie Ann B.; C. Makilan, Novemay; Langcoy, Mary Grace F.; Acanto, Ricky B. (Edelweiss Applied Science and Technology, 2024)
Plant extracts are valuable natural resources with diverse applications in pharmaceutical and food industries that can enhance science educa-tion by connecting theoretical knowledge to real-world applications, fostering critical thinking, and promoting environmental awareness. The study aimed to design and evaluate contextualized instructional materials for Grade 7 Science, focusing on integrating Blue Porterweed (Stachytarpheta jamaicensis), a locally abundant medicinal plant, into the curriculum to address the limitations of traditional rote learning methods. The research utilized the ADDIE model, which guided the process through its phases: Analysis, Design, Development, Implementa-tion, and Evaluation. Expert evaluators, science teachers, and Grade 7 students participated in the study to ensure the materials’ effectiveness and relevance. Data was collected using the standard Learning Resource Management and Development System (LRMDS) Evaluation Rating Sheet and researcher-developed questionnaires, validated using Lawshe’s Content Validity Ratio to ensure validity, and employed the In-ter-class Correlation Coefficient (ICC) to assess reliability. The findings revealed that the developed instructional materials—which included a module, lesson plan, learner activity sheets, and a teacher’s guide—met high-quality standards. Additionally, these materials significantly enhanced student engagement and motivation. The study concluded that contextualized instruction positively impacts science education out-comes. The study recommends the broader adoption of such instructional materials in educational settings and suggests further research to explore their long-term effects and potential applications in other subject areas.